Work Life Balance of Employees in Insurance Sector – A Comparative Analysis of Public and Private Sector in Kerala: Exploring the Work Life Balance of Employees in the Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The fast pace economic development in 20th century, across the globe has created new endeavors for the business organizations. Globalization has changed the world into a global village. This change has pushed the organizations for striving hard to gain and sustain their competitive advantage, by reducing cost, increasing profits and enhancing the operations. The changing world scenario also evoked the changes in the organizational culture. Organizational changes due to downsizing, mergers acquisitions and radical changes in technology have changed the work setups. The employees in present are more involved in their jobs than in the last decade. The long working hours, work pressure, high demanding jobs, use of sophisticated technology made it difficult for employees to keep a balance between their job and work commitments. This situation gave rise to the greatest challenge of human resource management issue i.e. Work Life Conflict (WLC). A person plays different role in the span of life, which include roles from work (worker, employer) and non-work (parent, spouse, friend, sibling, etc). Work Life Conflict (WLC) exists when time and energy demands to satisfy one role make it difficult to participate in other (Duxbury, 2001). Work life conflict also defined “as push and pull between family and work responsibilities, Nancy R Lockwood,(2003).